Jo's boys - Alcott, Louisa May, 1832-1888 (Mumbai : Wilco International, 2024)
Ten years after Jo opened a school for boys, the little men have grown up and left Plumfield. Now college students, sailors, and musicians, they each explore the world and try to find their place in it. But as they encounter love, disappointment, tragedy, and intrigue, the boys rely on Jo to help them through the challenges they face. Inspired by Alcott's own experiences, Jo's Boys brings the classic Little Women series to a close, completing the story that has inspired numerous film adaptations and that touches readers' hearts as much today as at its original publication.
Keywords: Class reunions -- Fiction; Domestic fiction